Prevalência de sintomas depressivos na gestação e fatores associados - Moraes, Eleomar Vilela de (2016)
Introduction: Psychic suffering is a characteristic of depressive symptoms carrier. When it occurs in pregnancy, it is a predictor of post-partum depression, abortion, and pre-eclampsia, and an increase of premature and surgical deliveries. Thus, the article aimed to analyze depressive symptoms and factors associated in pregnant women during prenatal care. Methods: Cross-sectional descriptive study, whose sample consisted of 375 pregnant women assisted during prenatal care in two important Public Hospitals in Goiânia, GO, Brazil, between September 2014 and May 2015. Social, economic, demographic, psychological, obstetric and behavioral data were collected. To assess the depressive symptoms among the pregnant women, the Hospital Anxiety and Depression Scale (HAD), which is internationally recognized and validated in Brazil, was used. Data were analyzed with the assistance of EPI-INFO® software, version 7.1.5. The calculation of Cronbach’s alpha coefficient was done with the Statistical Package software for Social Sciences (SPSS) version 21.0. For the correlation analyzes of variables, the Fisher’s Exact test, Mantel-Haenszel, Chi-Square and Prevalence Ratio were used, considering statistically significant the p-value associated lower or equal to 0.05 (p≤0.05) with a 95% Confidence Interval (95% CI). Ethics Committee in Research from Hospital das Clínicas of UFG (process nº 786.358 approved the research). Results: Depressive symptoms has reached 40.80% of the interviewed women, while 25.33% of them had moderate symptoms. The sample consisted mostly of young pregnant women, where 41.87% of them had completed only high school; 56.00% earned up to two minimum wages and the prevalence of alcohol ingestion by their partners was 45.11%. After multivariate analyses it was evident that, “suffered emotional/psychological violence” (OR=6.224), “single/separated” (OR=3.020), “prior mental problem” (OR=3.042), “obstetric complications during current pregnancy” (OR=2.347) and “alcoholism by pregnant in the first three months” (OR=2.230), showed association with symptoms of depression. In addition, “perform physical activity during pregnancy” (OR=0.266) and having “alcohol-abstinent partner” (OR=0.403) had a protective relationship to the emergence of depressive symptoms. Conclusions: The prevalence of probable depressive symptoms among the participants is 15.47%. The importance of ascertaining the screening of gestational depression if the woman is single, if there is emotional violence, obstetric problems during pregnancy and the consumption of alcohol by the woman or by her partner.